Turkey : 2002 Article IV Consultation and First Review Under the Stand-By Arrangement-Staff Report; Staff Statement; Public Information Notice and News Brief on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2002)
This paper examines Turkey's 2002 Article IV Consultation and First Review Under the Stand-By Arrangement (SBA). In response to September 11, the Turkish government initiated a new intensified IMF-supported program, both to protect the economy against future crises, and to continue Turkey's ambitious reform agenda. Under the 2002-04 Program, the continuation of the float will limit the potential for speculative attacks. Ongoing financial sector reform together with corporate sector restructuring will help strengthen the banking and business sectors, and continued fiscal discipline should foster medium-term debt sustainability.